Microbial fuel cell enhanced pollutants removal in a solid-phase biological denitrification reactor: System performance, bioelectricity generation and microbial community analysis. (December 2021) - Zhao, Chuanfu; Liu, Bing; Meng, Shuangyu; Wang, Yihua; Yan, Liangguo; Zhang, Xinwen; Wei, Dong
Graphical abstract: Highlights: The preposition removal of MO by anode promoted the removal of Cr (VI) and NO3 – -N. MFC contributed to the decrease of the final effluent SMP content. A strong symbiotic network was found in the anode and denitrifying biofilm. Abstract: A novel electrochemical system of microbial fuel cell (MFC) coupled solid-phase denitrification biofilm reactor (DBR) system was established to explore the effect of simultaneous power generation and pollutant removal under different HRTs (Ⅰ:48 h; Ⅱ :24 h). The average removal rates of methyl orange, Cr (VI) and NO3 – -N in test group were 93.0, 98.6 and 95.5% within 60 days, while those were 53.1, 72.1 and 72.7% in control. The maximum power density was 61.2 (Ⅰ) and 16.1 mW/m 2 (Ⅱ), while average output voltage was 122 (Ⅰ) and 83.6 mV (Ⅱ). Components 1 and 2 in soluble microbial products were identified, and the humic-like and fulvic acid-like substances varied through different layers. Pseudomonas produced electricity in anode, while denitrified in denitrification layer. Importantly, symbiotic cooperation was absolutely dominant in network analysis of both anodic and denitrifying biofilms. MFC significantly improved DBR's ability to treatment co-polluted wastewater.